A rare occurrence of complicated plasmodium vivax malaria in a 5-month-old infant - Bainade, Kapil; Kotrashetti, Veeranna; Elon, Neelu; Dhulaj, Apoorva (International Journal of Contemporary Pediatrics, 2025)
Malaria is less frequently documented in infants under six months due to a focus on older populations in research. Despite protective maternal antibodies and fetal hemoglobin, infants in this age group remain susceptible to malaria. This case highlights the importance of recognizing and diagnosing malaria in this vulnerable population. Recognition and appropriate management are crucial to preventing severe complications and improving patient outcomes. It presents a diagnostic dilemma in infants under 6 months when distinguishing malaria from sepsis, as both conditions present with similar symptoms.